Usability assessment and improvement strategy of music APP interface based on heuristic evaluation - Chao Zhou; Hongyuan Zhao (Humanities & Social Sciences Communications)
Abstract With the increasing diversification of virtual interface functionality and services, excessive cognitive and operational loads are posing new challenges to the usability of music app interfaces. This study investigates whether interfaces characterized by integrated functionality and complex operational processes effectively meet users’ usability requirements. Through a heuristic evaluation methodology, 15 independent evaluators assessed the interface usability of the QQ Music App. The evaluation identified several critical usability issues, including inadequate visual hierarchy, insufficient distinctiveness in functional elements, excessive use of pop-up interfaces, and limited operational feedback mechanisms. This research indicates that interface usability and product competitiveness can be enhanced by using multiple strategic methods: optimizing the information load of the online music application interface, enhancing the visibility of common interface functions while simplifying operational processes, incorporating interactive prompts for popup management, and delivering interface feedback that corresponds with users’ contextual engagement with the online music application. The effectiveness of these strategies was additionally corroborated through prototype creation and usability testing. This study’s findings provide novel insights for design techniques applicable to music app development teams.